A list of eclectic viruses, virus-like diseases and viroids of grapevines that should not be considered for regulatory oversight: a global plea from virologists - Fuchs, Marc; Rwahnih, Maher Al; Blouin, Arnaud G.; Burger, Johan; Chooi, Kar Mun; Constable, Fiona; Ertunc, Filiz; Fiore, Nicola; Habili, Nuredin; Hily, Jean-Michel; Katis, Nikolaos; Lemaire, Olivier; et al. (Journal of Plant Pathology, 2025)
Grapevine ( Vitis spp.) propagation material is profusely exchanged across geographic and regulatory boundaries. Trading germplasm increases the diversity of cultivars and rootstocks with enhanced viticultural attributes but also risks the dissemination of pests and detrimental pathogens such as viruses in new grape production areas. Therefore, regulations are established to facilitate the safe trade of Vitis propagation material with desirable traits. Regrettably regulations are sometimes inadequate. Consequently, the accessibility of desired germplasm for growers might be unduly delayed, providing opportunities to circumvent regulations by illegally introducing germplasm of interest, amidst risking epidemics of viruses of concern, including quarantined agents, and jeopardizing the health of vineyards. To address some of the regulatory limitations, scientists from around the world recently defined phantom agents in fruit crops, including grapevines, and provided a compelling case for their exclusion from regulatory oversight. Simultaneously, a group of virologists realized the need to complement the list of phantom agents in grapevines by considering additional viruses, virus-like diseases and viroids that should not be subject to regulatory oversight. Here, we present a list of nine viruses, 14 virus-like diseases, nine viroids, and 129 presumed viruses of the grapevine, that are not phantom agents but should be excluded from regulation or should not be regulated. Our list is anticipated to assist policy makers adopt regulations that expedite the safe exchange of Vitis germplasm across regulatory boundaries while reducing incentives for illicit introductions.